Pemanfaatan Teknologi Pompa Portabel Tenaga Surya untuk Sistem Irigasi Kebun - Jaya, Harie Satiyadi; Rahmat, Hudan; Sukardi, Sukardi (LPPM Universitas Palangka Raya, 2023)
The Community Service Program (PKM) aims to solve the problems faced by farmer group partners, such as: (1) unequal financial capabilities in each member of the farmer group, (2) less good agricultural yields if smoke appears during the long dry season, and (3) high operational costs because they depend on fuel consumption for the plant watering process. The implementation of core activities in this PKM program consists of two stages, namely; (1) solar cell pump assembly training to provide solutions for partners who are not familiar with solar-powered portable water pump technology and still depend on using fuel pumps as a means of watering plants, and (2) solar cell pump operation and maintenance training to provide solutions for partners who cannot operate and maintain solar-powered portable water pumps.